Evaluation of horizontal condylar guidance on a fully adjustable articulator at varying protrusive distances: An in vivo study - Jayant N. Palaskar; Amit Dhansukhlal Hindocha; Nikhil Joshi; Ketaki Balsaraf (The Journal of Indian Prosthodontic Society)
Aim: This study aimed to assess the accuracy of HCG values obtained with records at various protrusive distances on a fully adjustable articulator. Settings and Design: Pantographs are used for condylar settings on a fully adjustable articulator but are complex and time-consuming. Protrusive interocclusal records can be used to set horizontal condylar guidance (HCG) in fully adjustable articulators; however, the ideal protrusive distance to do so remains unclear. This was an in vivo observational cross-sectional study. Materials and Methods: Twenty-five dentate subjects participated in this study. Customized guides with calibrations at 2, 4, 6, and 8 mm were used to create protrusive interocclusal records at each increment. The HCG values derived from these records were set on a fully adjustable articulator (Denar D5A, Whip Mix Corp.). For control, standardized digital lateral cephalograms of each subject were taken in edge-to-edge and maximal intercuspal positions. These cephalograms were superimposed using Dolphin Imaging software (Dolphin Imaging and Management Solutions), allowing the determination of the cephalometric HCG angle by measuring the intersection between a line passing from the Condylion and the Frankfort horizontal plane. The HCG values from the articulator were compared with the cephalometric HCG values. Statistical Analysis Used: Statistical analysis was conducted using repeated measures ANOVA for intragroup comparison and one-way ANOVA with Bonferroni post hoc tests for intergroup comparisons. The Shapiro–Wilk test was conducted to assess normality. Results: The mean HCG values obtained at 2, 4, 6, and 8 mm were 49.92°, 44.28°, 36.60°, and 26.60°, respectively, while the cephalometric HCG value was 44.51°. Analysis revealed no significant difference between the cephalometric HCG and the 4 mm record (P > 0.05), but significant differences were noted at 2, 6, and 8 mm (P < 0.05). Conclusions: The HCG set on the Denar D5A articulator using a 4 mm protrusive interocclusal record closely matched the cephalometric HCG, suggesting that a 4 mm record may be optimal when using protrusive records for programming this articulator.